2006
DOI: 10.1016/j.jhsb.2005.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Compression Neuropathy after Fractures of the Distal Radius

Abstract: Sixty patients with unilateral distal radius fractures were managed conservatively. Clinical assessment included objective and subjective evaluations of the outcome of treatment. Radiographic evaluation included fracture classification using the AO/ASIF system and measurement of volar tilt, radial inclination and radial height shortening at the end of treatment. Clinical signs of carpal tunnel syndrome were confirmed electrodiagnostically in 12 patients (20%) during the recovery period. Each patient had electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 44 publications
0
42
0
6
Order By: Relevance
“…This view is supported by the study of Bienek et al, who observed a significant correlation between clinical outcome and posttraumatic median nerve compression neuropathy after nonsurgical treatment of distal radius fractures. 18 However, functional outcome was similar in both groups in the later course. Final functional outcome was reached within 6 months after trauma.…”
Section: Functional Outcomesmentioning
confidence: 82%
See 1 more Smart Citation
“…This view is supported by the study of Bienek et al, who observed a significant correlation between clinical outcome and posttraumatic median nerve compression neuropathy after nonsurgical treatment of distal radius fractures. 18 However, functional outcome was similar in both groups in the later course. Final functional outcome was reached within 6 months after trauma.…”
Section: Functional Outcomesmentioning
confidence: 82%
“…There might be a relationship between impaired grip strength and median nerve dysfunction, as grip strength improved with decreasing median nerve irritation. 18 At the latest follow-up, grip strength was balanced between the 2 groups when only 4 patients with persisting median nerve irritation remained in the CTR group and none in the HRY group. It is acknowledged that the approach is only 1 factor to influence the functional outcome.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Bienek et al reported delayed CTS, confirmed by electrodiagnostic testing, in 12 of 60 patients (20%) at an average onset of 10 months after distal radius fracture. 15 In a retrospective study of 49 surgically treated distal radius fractures, Jupiter et al reported delayed CTS in 3 cases (6%), all of which were secondarily treated with release of the TCL. 25 In another retrospective study by Ruch and Papadonikolakis, 2 of 16 surgicallytreated distal radius fractures required additional surgery for delayed CTS.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Some surgeons also advocate adjunctive prophylactic CTR for fractures with substantial comminution or displacement 3,6,9 -14 or in patients who cannot reliably report sensory deficits after surgery, such as patients with polytrauma or head injuries or those who are intubated. 3 Although delayed CTS has been reported in as many as 20% of patients with distal radius fractures, 15 the role of prophylactic CTR in patients without signs or symptoms of median nerve dysfunction at the time of fracture fixation remains controversial. 3,16 -19 To effectively decompress the median nerve at the time of fracture fixation, the transverse carpal ligament (TCL) is typically divided through either a separate proximal palm incision or extension of a volar Henry approach across the wrist flexion crease.…”
mentioning
confidence: 99%
“…[38] Kompleks bölgesel ağrı sendromu Kompleks bölgesel ağrı sendromu (KBAS); bölgesel ağrı, otonom disfonksiyon, vazomotor değişiklikler, atrofi ve fonksiyonel kayıp ile karakterize, patognomik tanısal testi olmayan klinik bir tablodur. Bu sendrom, refleks sempatik distrofi, kozalji, algodistrofi olarak da bilinir.…”
Section: Karpal Tünel Sendromuunclassified